Harry potter and the prisoner of azkaban - Rowling, J. K. (London : Bloomsbury Publishing, 1999)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.
"Year 3"--Spine.
Sequel to: Harry Potter and the Chamber of Secrets.
Sequel: Harry Potter and the goblet of fire.
Keywords: Wizards -- Fiction; Magic -- Fiction